Pengaruh Perubahan Tarif PPN terhadap Real Estate Purchase Intention dengan Lifestyle sebagai Variabel Moderasi: Pengaruh Perubahan Tarif PPN terhadap Real Estate Purchase Intention dengan Lifestyle sebagai Variabel Moderasi - Valerie Kristiono; Santi Novita (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2024)
The enactment of Undang-Undang Nomor 7 Tahun 2021 Tentang Harmonisasi Peraturan Perpajakan caused the 10% VAT rate to change to 11%. The increase in VAT rates is intended to restore economic conditions but at the same time exacerbate the amount of VAT that must be borne by buyers when investing in real estate. This study aims to obtain evidence about the effect of changes in VAT rates on purchase intentions of real estate consumers with lifestyle as a moderating variable. Primary data was obtained from a questionnaire with 205 respondents aged 18 years and over. The data collected will be analyzed through linear regression analysis and moderation regression analysis. The results of the study show that changes in VAT rates have a positive effect on purchase intention. VAT can indeed burden buyers because it in-creases the price that must be paid but at the same time it can also increase purchase intention if the change in VAT rates reflects a social contract between consumers and the government. In addition, lifestyle has not been proven to moderate the effect of changes in VAT rates on purchase intention, but rather has a direct effect on pur-chase intention. Based on additional analysis, it was found that life-style acts as a pseudo moderator for respondents with an accounting background but acts as a mod-erating predictor for respondents who do not have an accounting background. This proves the occurrence of mental accounting.